A puzzle - Martin, Juliet (Thomas Nelson South Melbourne, 1994)
A Puzzle by Juliet Martin is likely a children's or young adult book that revolves around the theme of solving a mystery or figuring out a complex situation. The story may follow a character who encounters a riddle, problem, or literal puzzle that requires ingenuity, patience, and critical thinking to solve. Along the way, the protagonist might learn important life lessons about perseverance, teamwork, or self-discovery. With its engaging storyline, the book could appeal to readers who enjoy mysteries and challenges, blending suspense with character development.